Sementes de arroz infestadas com gorgulhos do gênero Sitophilus: análises fisiológicas, de imagens e composição centesimal - Briceño Pinzón, Ivan David (2023)
The examination of seeds infested with insect pests can be time consuming, tiring and destructive, in addition to making the seed unfeasible for possible later testicles. Controlled methodologies in the use of X-rays have proven to be accurate, efficient and fast, allowing the verification of the integrity of the internal tissues without the need to section the seed. The objective of this work was to evaluate the infestation of rice seeds with Sitophilus sp. (Coleoptera: Curculionidae) through radiographic images, as well as the physiological quality and proximate composition of the seeds. For this, an experiment was carried out to detect the stages of development of Sitophilus spp. and identify the damage caused by the insect through radiographic images in rice seeds. Seeds of the CMG-1590 cultivar were infested and the assessments were based on the different days after infestation. Statistical differences were observed in the percentages of infestation detected by X-rays in the evaluated treatments, in addition, the test allowed identifying the stages of development of egg, larva and adult. In the second experiment, the objective was to analyze the physiological quality and proximate composition of rice seeds subjected to different levels of infestation with Sitophilus spp., detected by radiographic images. Statistical differences (p<0.05) in the analyzes of physiological quality were detected between the evaluated infestation levels. The percentage of germination, first count and seedling emergence decreased as the level of infestation increased; however, a higher electrical conductivity was found. In the proximate composition of the seeds, no statistical differences (p>0.05) were observed between the infestation levels for the percentages of starch, crude protein, ether stratum and crude fiber. In the third experiment, analyzes of radiographic images of seeds infested with Sitophilus spp. of rice cultivars C1 (P85-15-CNA), C2 (CMG-1590) and C3 (OBS 1819) were carried out. Through the ImageJ® software, information on the area, perimeter, relative and integrated density was extracted, as well as on the gray distribution profiles, where statistical differences were observed between the seeds with the presence of the weevil development stages and the healthy seeds, seeds with adult and empty seeds obtained the lowest values of these parameters.